The Importance of Glucose in Medicine - o’g’li, Qurbonov Og’abek Khayrulla; qizi, Ne’matova Zulayho Jamol (American Journal of Biomedicine and Pharmacy, 2025)
This article provides an overview of glucose, including its properties, associated disorders, and medical applications. The physiological role of glucose in the human body is discussed, along with the consequences of its imbalance, such as hypoglycemia and hyperglycemia. The article also highlights the clinical use of glucose solutions in medicine, including their application for energy supply, hydration, detoxification, parenteral nutrition, and treatment of hypoglycemia. Different concentrations of glucose solutions (5%, 10%, 20%, and 40%) and their specific indications are explained. The study emphasizes the importance of glucose as a vital substrate for metabolic processes and its critical role in maintaining homeostasis and supporting patient care in various clinical situations.